Effect of Increasing Number of Nodes on Performance of SMAC, CSMA/CA and TDMA in MANETs - Khan, Samiullah; Faisal, Farooq; Nawaz, Mahmood; Javed, Farkhanda; Khan, Fawad Ali; Noor, Rafidah Md; -, Matiullah; Zia, -; Shoaib, Muhammad; Usman, Faqir (SAI Organization, 2018)
The importance of Wireless Sensor Network (WSN) increases due to deployment for geographical, environmental and surveillance purpose in war fields. WSN facing several challenges due to its complex nature including key problems, such as routing and medium access control protocols. Several approaches were proposed for the performance evaluation of WSN on the basis of these issues due to the fact that MAC layer access protocols have a great impact on the performance of WSN. In this paper, we investigated the performance evaluation of three well known MAC Access protocols, i.e. sensor medium access control protocol (SMAC), carrier sense multiple access with collision avoidance (CSMA/CA), and time division multiple access (TDMA) over adhoc on demand distance vector (AODV) routing protocol. The number of simulation scenarios were carried out by using NS- 2, the simulation metrics used are throughput, end-to-end delay and energy consumed. Simulation results showed that SMAC out perform CSMA/CA and TDMA by consuming less energy, less end to end delay and high throughput due to contention based approach to access the medium for transmission.